Molecular and biochemical responses of sesame (Sesame indicum L.) to rhizobacteria inoculation under water deficit - dos Santos, Anderson Reges; da Rocha, Geisenilma Maria Gonçalves; Machado, Alexandre Paulo; Fernandes-Junior, Paulo Ivan; Arriel, Nair Helena Castro; Gondim, Tarcisio Marcos de Souza; de Lima, Liziane Maria (Frontiers in Plant Science, 2024)
Water scarcity is a challenge for sesame cultivation under rainfed conditions. In this scenario, a potential strategy to alleviate the water deficit is the application of plant growth-promoting bacteria. The objective of this study was to analyze the interaction of rhizobacteria with sesame cultivation under water deficit conditions. An experiment was conducted in pots in a greenhouse using the BRS Morena sesame cultivar. The experimental design was completely randomized in a factorial scheme: 2 (irrigation regimes -daily irrigation and water deficit by suspending irrigation until 90% stomatal closure) x 6 (treatments with nitrogen or inoculants), with 5 replications. The types of fertilization were characterized by the addition of nitrogen (ammonium sulfate;, 21% N), inoculants based on Bacillus spp. (Ppant001, ESA 13, and ESA 402), Agrobacterium sp. (ESA 441), and without nitrogen (control). On the fifth day after the suspension of irrigation, plant material was collected for gene expression analysis (DREB1 and HDZ7), activities of antioxidant enzymes (superoxide dismutase and catalase), relative proline content, and photosynthetic pigments. At the end of the crop cycle (about 85 days), production characteristics (root dry matter, aboveground dry matter, number of capsules, and thousand seed weight), as well as leaf nitrogen (N) and phosphorus (P) content, were evaluated. There was a positive effect on both production and biochemical characteristics (proline, superoxide dismutase, catalase, and photosynthetic pigments). Regarding gene expression, most of the inoculated treatments exhibited increased expression of the DREB1 and HDZ7 genes. These biological indicators demonstrate the potential of rhizobacteria for application in sesame cultivation, providing nutritional supply and reducing the effects of water deficit.